Role of antioxidants in reducing oxidative stress and seizure frequency in drug-resistant epileptic patients - Ismy, Jufitriani; Soebadi, Amanda; Mangunatmadja, Irawan; Monica, Merci; Sari, Teny T.; Yuliarti, Klara (Narra Sains Indonesia, 2024)
Drug-resistant epilepsy presents significant challenges in treating epileptic patients, leading to recurrent seizures and necessitating the use of polypharmacy with anti-epileptic drugs. Both of these conditions contribute to increased oxidative stress, which is detrimental to the brain. The aim of this study was to determine the role of vitamins C and E in reducing oxidative stress and seizure frequency in drug-resistant epileptic patients. This was a double-blinded, randomized clinical trial with a placebo, parallel design, and block randomization. The subjects were drug-resistant epileptic patients aged 1–18 years who received routine treatment. Randomization was performed on 100 patients who were divided into the treatment or placebo groups. The patients received a combination of vitamin C (100 mg/day) and vitamin E (200 IU/day for those <5 years or 400 IU/day for those ≥5 years) or a placebo for eight weeks. Malondialdehyde (MDA) levels and seizure frequency were measured prior to and after the intervention. A total of 42 and 46 patients were followed till the end of the study in the intervention and placebo groups, respectively. Our data indicated that the MDA levels prior to treatment were not significantly different between the treatment and placebo groups (0.901 vs 0.890 mmol/mL, p=0.920) and were significantly reduced after the treatment in both the treatment group (p<0.001) and placebo group (p=0.028). The changes in MDA levels (between post- and pre-treatment) were also not significantly different between the two groups (p=0.181). Our per-protocol analysis indicated that the reduction in seizure frequency was significantly higher in the treatment group compared to the placebo group (95% vs 35%, p<0.001), with 92% and 60% relative and absolute risk reduction, respectively. The intention-to-treat analysis also indicated that the reduction in seizure frequency was significantly higher in the intervention group than in the control group (80% vs 32%, p<0.001), with relative and absolute risk reduction of 70% and 48%, respectively. There was no significant relationship between changes in MDA levels and seizure frequency in either group. In conclusion, vitamins C and E could reduce seizure frequency and, therefore, could be considered as adjuvant therapy in drug-resistant epileptic patients.